Economic Evaluation of the Efficiency of Supply Chain Management in Agricultural Production Based on Multidimensional Research Methods - Alisa M. Ableeva; Guzel A. Salimova; Nuria T. Rafikova; Ilvir I. Fazrahmanov; Zaria A. Zalilova; Tatiana N. Lubova; Gulnara R. Nigmatullina; Irina N. Girfanova; Fanisa F. Farrahova; Aigul M. Hazieva (International Journal of Supply Chain Management, 2019)
The article studies the system of indicators characterizing the efficiency of supply chain management in agricultural production. The hierarchical classification of the subjects of the Russian Federation according to the indicators characterizing the results of the activity of the agricultural sector has been carried out. Clusters with high, medium and low levels of supply chains management’s efficiency have been identified. Regions for selected clusters are set. A comparative analysis of the regions on the performance of the agricultural sector has been carried out. Regularities are revealed, prospects for further development are defined. For each cluster promising areas of effective development of agriculture were identified.